Peningkatan Kualitas Udang Rebon Kering Multirespon Mengintegrasikan Metode Taguchi Gray Relational Analysis dan Principal Component Analysis - Nabila Rahmawati; M. Hanifuddin Hakim; Ridho Akbar; Ridho Akbar (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2023)
Rebon shrimp is the catch of fishermen around Sukolilo Baru area, Bulak District of Surabaya. Rebon shrimp processing is only sorted and then dried and sold to collectors. However, the drying process has no definite parameters of factors that can affect the quality of dried rebon shrimp. In overcoming this, research was conducted on improving the quality of dried rebon shrimp. The increase certainly raised several quality responses, namely the color and moisture content of rebon shrimp. The resulting multiresponse needed to be converted into a single response. To optimize multiresponse into a single response, the Taguchi method was used in combination with the Gray Relational Analysis (GRA) and Principal Component Analysis (PCA) methods. Factors and levels were the volume of rebon shrimp (A) with levels of 4 Kg, 4.5 Kg, and 5 Kg, drying time (B) with levels of 90 minutes, 120 minutes, and 150 minutes, and drying temperatures (C) with levels of 41-44ºC, 45-49 ºC, and 36-40 ºC. The quality characteristics were nominal that was the best (if the resulting value is close to the target value, the quality is better). The result produced PCA weighting values on PC1 as evidenced by eigen>1 values. The optimal combination is the volume factor of rebon shrimp at the level of 4.5 Kg, the drying time factor of 120 minutes, and the drying temperature factor of 45 – 49 ºC.